Obraz w służbie mnichów. Średniowieczna pieczęć konwentu z opactwa cysterskiego w Krzeszowie - Kałuski, Tomasz (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2018)
The article discusses the function of the oldest conventual seal of the Cistercian abbey in Krzeszów. Based on the fullest possible source material, the circumstances around the introduction of the seal into the abbey are presented. The significance of the image on the seal and the most probable source of inspiration for the creation of this image are examined. The role of the seal of the Krzeszów convent in the documents issued in the abbey is also discussed, along with the chronology of the seal’s use.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne